Treatment of Ready-To-Eat Cooked Meat Products with Cold Atmospheric Plasma to Inactivate Listeria and Escherichia coli - Isabella Csadek; Ute Vankat; Julia Schrei; Michelle Graf; Susanne Bauer; Brigitte Pilz; Karin Schwaiger; Frans J. M. Smulders; Peter Paulsen (Foods, 2023)
Ready-to-eat meat products have been identified as a potential vehicle for Listeria monocytogenes. Postprocessing contamination (i.e., handling during portioning and packaging) can occur, and subsequent cold storage together with a demand for products with long shelf life can create a hazardous scenario. Good hygienic practice is augmented by intervention measures in controlling post-processing contamination. Among these interventions, the application of ‘cold atmospheric plasma’ (CAP) has gained interest. The reactive plasma species exert some antibacterial effect, but can also alter the food matrix. We studied the effect of CAP generated from air in a surface barrier discharge system (power densities 0.48 and 0.67 W/cm2) with an electrode-sample distance of 15 mm on sliced, cured, cooked ham and sausage (two brands each), veal pie, and calf liver pâté. Colour of samples was tested immediately before and after CAP exposure. CAP exposure for 5 min effectuated only minor colour changes (ΔE max. 2.7), due to a decrease in redness (a*), and in some cases, an increase in b*. A second set of samples was contaminated with Listeria (L.) monocytogenes, L. innocua and E. coli and then exposed to CAP for 5 min. In cooked cured meats, CAP was more effective in inactivating E. coli (1 to 3 log cycles) than Listeria (from 0.2 to max. 1.5 log cycles). In (non-cured) veal pie and calf liver pâté that had been stored 24 h after CAP exposure, numbers of E. coli were not significantly reduced. Levels of Listeria were significantly reduced in veal pie that had been stored for 24 h (at a level of ca. 0.5 log cycles), but not in calf liver pâté. Antibacterial activity differed between but also within sample types, which requires further studies.